Multiple arterial dissections and connective tissue abnormalities - Erhart, Philipp; Körfer, Daniel; Dihlmann, Susanne; Qiao, Jia-Lu; Haußer-Siller, Ingrid; Ringleb, Peter A.; Männer, Jörg; Dikow, Nicola; Schaaf, Christian P.; Grond-Ginsbach, Caspar; Böckler, Dittmar (Journal of Clinical Medicine, 2022)
Background: Although patients with multiple arterial dissections in distinct arterial regions rarely present with known connective tissue syndromes, we hypothesized that mild connective tissue abnormalities are common findings in these patients. Methods: From a consecutive register of 322 patients with cervical artery dissection (CeAD), we identified and analyzed 4 patients with a history of additional dissections in other vascular beds. In three patients, dermal connective tissue was examined by electron microscopy. DNA from all four patients was studied by whole-exome sequencing and copy number variation (CNV) analysis. Results: The collagen fibers of dermal biopsies were pathologic in all three analyzed patients. One patient carried a CNV disrupting the COL3A1 and COL5A2 genes (vascular or hypermobility type of Ehlers-Danlos syndrome), and another patient a CNV in MYH11 (familial thoracic aortic aneurysms and dissections). The third patient carried a missense substitution in COL5A2. Conclusion: Three patients showed morphologic alterations of the dermal connective tissue, and two patients carried pathogenic variants in genes associated with arterial connective tissue dysfunction. The findings suggest that genetic testing should be recommended after recurrent arterial dissections, independently of apparent phenotypical signs of connective tissue disorders.